Poro-Elastic Theory with Applications to Transport in Porous Media - Jeng, Dong-Sheng (Taylor & Francis, 2023)
This book treats the subject of porous flow and its applications in three engineering and scientific problems. The first major part of the book is devoted to solute transport in unsaturated porous media. Dynamic hydraulic conductivity and degree of saturation associate with pore pressures are also included in the consolidation-induced solute transport process. The second part of this book focuses on tidal dynamics in coastal aquifers, including shallow water expansion for sloping beaches, two-dimensional problem in estuarine zone and leaky confined aquifers. The final part of the book summarizes the recent development of porous model in the field of liquefaction around marine infrastructures including fundamental mechanisms of momentary and residual seabed liquefaction, two-dimensional and three-dimensional porous models for fluid-seabed interactions around breakwaters, pipelines and piled foundations in marine environments. The authors' aim is to describe in detail the applications of porous models for several engineering problems. This book will provide academic researchers and industry an overview of recent development in the field of porous models and the applications. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Funded by Qingdao University Technology, China